Ultrasensitive Colorimetric and Ratiometric Detection of Cu2+ - Fanna, Daniel J. (2019)
Herein, we report the synthesis and characterization of a chemosensor, 5-(diethylamino)-2-(2,3-dihydro-1H-perimidin-2-yl)phenol (HL), synthesized from a condensation between 4-(diethylamino)salicylaldehyde and 1,8-diaminonaphthalene. Upon investigation of the sensing properties of HL, it was found that this sensor may be employed for simple yet efficient detection of Cu2+ in aqueous methanol solutions. The selective and ratiometric response to Cu2+ yielded an outstandingly low limit of detection of 3.7 nM by spectrophotometry and is also useful as a naked-eye sensor from 2.5 μM. The system was studied by spectrophotometric pH titrations to determine Cu2+ binding constants and complex speciation. Binding of Cu2+ to HL occurs in 1:1 stoichiometry, in good agreement with high-resolution electrospray ionization mass spectrometry (ESI-HRMS) results, Cu2+ titrations, and Job's plot experiments, while the coordination geometry was tentatively assigned as square pyramidal by spectroscopic studies.